Successful Treatment of Invasive Aspergillosis in a Heart Transplant Patient - Radovancevic, Branislav (1985)
Infection continues to be a major cause of mortality in cardiac transplant patients, and even though there has been significant progress in diagnosing and treating many infectious disease problems, invasive aspergillosis in the transplant patient represents a serious and usually fatal complication. Even with successful early diagnosis, the use of free amphotericin B (a polyene antibiotic) has failed to cure disseminated infection. We report the case of a 46-year-old transplant patient who failed to respond to treatment with free amphotericin B after a 7-day period of treatment for biopsy-proven pulmonary aspergillosis. However, a subsequent substitution of a liposomal form of amphotericin B was used, and the patient responded well to a total dose of 1.5 mg. After 7 months, the patient continues free of infection. This experience suggests that the introduction of liposomal amphotericin B may give new hope for treating an otherwise lethal infection.